Takaful standards and customer perceptions affecting Takaful practices in Malaysia - Parimala Devi, Ponnan (2022)
The objectives of this study is to investigate the factors of perceived benefits of sales promotion, perceived adequacy of premium, perceived adequacy of information, and perceived quality affect customer perceptions toward Takaful practices in Malaysia. This study mainly used questionnaires to collect evident whereby the data have gathered based on the answer from the respondent. This data analysed using Statistical Package for Social Sciences (SPSS) Version 23 software. The collected data analysis based descriptive analysis, factor analysis, reliability analysis, correlation analysis and regression analysis. Based on finding, the factors perceived benefits of sales promotion, perceived adequacy of information and perceived quality are the essential factors that significantly influences customer perception toward Takaful practices in Malaysia. The Perceived adequacy of premium is factors that are not significantly influence customer perception toward Takaful practices in Malaysia. Henceforth, the Takaful industry needs to aim on factors such as sales promotion, adequacy of information and quality of service of Takaful companies to be equally successful in the insurance industry.